Anti-inflammatory and antidisbiotic effect of oral biothrit-denta fytogel at orthodontic operations in patients with dentoalveolar anomalies - Azari, Mohammed Ali Mehrdad (Journal of Education, Health and Sport, 2019)
Background. To determine the condition of the oral cavity in persons with dentoalveolar anomaly after orthodontic operations and the effect on it of oral applications of the Biotrit-Denta phytogel.Methods. A total of 20 patients with dental-maxillary anomalies and 13 healthy individuals were examined. In unstimulated saliva (oral fluid), the activity of elastase, catalase, lysozyme, urease and the content of malondialdehyde (MDA) were determined. The antioxidant-prooxidant index API was calculated using the ratio of catalase activity and MDA content, and the degree of dysbiosis was calculated using the ratio of relative activities of urease and lysozyme. All 20 patients underwent orthodontic surgery, of this number 10 patients received oral applications of the Biotrit-Denta phytogel for 30 days, the other 10 patients made up the comparison group. After 2 months, the above indicators were determined in all patients in saliva.Results. An increase in the activity of elastase, urease, the content of MDA and the degree of dysbiosis with a decrease in the activity of catalase and the API index was found in patients with dental-maxillary anomalies. Applications of the phytogel reduced the activity of elastase, urease, MDA content and the degree of dysbiosis, however, they increased the activity of catalase, the API index and showed a tendency to increase the activity of lysozyme. In the comparison group, there were no significant changes in the indicators.Conclusion. Dentoalveolar anomalies in patients in the oral cavity cause the development of dysbiosis and inflammation, a decrease in antioxidant and immune defense. Oral applications of phytogel "Biotrit-Denta" have antidisbiotic and anti-inflammatory effects.